F-response frequency in motor neuron disease and cervical spondylosis. Issue 5 (May 1987) - Peioglou-Harmoussi, S; Fawcett, P R; Howel, D; Barwick, D D
Abstract : During a train of 200 stimuli, F-response frequency, frequency of identical responses, and F-response shape were studied in the ulnar nerve of 17 patients with motor neuron disease (MND) and 16 patients with cervical spondylosis (CS). In MND patients, F-response frequency varied between 5% and 96% with a median of 39% which was significantly lower than controls (p less than 0.001), and showed a significant rank correlation with the M-response amplitude (r = 0.62, p less than 0.004). Identical responses occurred more frequently than in controls (median 30.8%, p less than 0.001). F-response frequency was normal in CS patients (median 76.3%, range 35% to 97%), but the frequency of identical responses (median 6.3%) was higher than normal (p less than 0.01). Reduced F-response frequency in MND was thought to reflect loss of lower motor neurons, while the presence of spasticity was probably the major factor underlying the increased frequency of identical responses in both disorders. F-response shape tended to be simpler in MND and rather more complex in CS patients than controls.